Sustainable development as successful technology transfer: Empowerment through teaching, learning, and using digital participatory mapping techniques in Mazvihwa, Zimbabwe. (2018) - Eitzel, M.V.; Mhike Hove, Emmanuel; Solera, Jon; Madzoro, Sikhangezile; Changarara, Abraham; Ndlovu, Daniel; Chirindira, Adnomore; Ndlovu, Alice; Gwatipedza, Shamiso; Mhizha, Memory; Ndlovu, Moses
Abstract: In development engineering, practitioners often strive to empower local communities through technology. Empowerment, however, is typically not well-defined and rarely assessed, leading to an erosion of its meaning. In this study, we define empowerment as capacity building through technology transfer, which we evaluate by assessing skill transfer, skill application, increased individual confidence, and community support. We test the usefulness of these assessments for participatory mapping as a form of technology transfer, using a Participatory Action Research approach. Our case is a digital mapping team embedded in the long-term community-based participatory research agenda of The Muonde Trust in Mazvihwa, Zimbabwe. We taught and evaluated mapping by conducting workshops and engaging in a variety of mapping projects (including measuring access to basic services, land-use planning, and cultural and historical preservation projects), demonstrating dramatically increased mapping skills and individual confidence, and the creation of a community of practice able to teach the skills. Our peer-based learning techniques used adult education principles and could be applied in creating other local communities of practice to support the use of medium-tech mapping methods (basic GPS units and computer mapping software). In poverty reduction and sustainability initiatives, participatory mapping can be complementary to cutting-edge big data approaches and necessary for true improvements in the well-being of the most vulnerable populations on our planet. Development engineers would benefit from incorporating participatory action research principles into their work, learning to co-labor with communities to define and solve problems. Highlights: We define empowerment using specific technology transfer outcomes. Communities of practice support open-ended, peer-based technology transfer. Effective adult education principles worked well with medium-tech mapping solutions. Local people used these skills to identify and solve their own development problems. Development Engineering benefits from using Participatory Action Research methods.